Regulating bodies: The discursive production of disability and disability research in the legal setting - Morton, Missy (Disability Studies Quarterly, 2006)
This article reports a qualitative study of six court cases that consider the admissibility of facilitated communication (FC) as evidence. While this is not a study of the legal system per se, I examine this system as a site where meanings of science, research, ability, and disability are contested. In order for a set of truths and practices to operate as legitimate in a particular institution, there is also a wider discourse and set of associated practices within which the received truths and practices of that institution come to be accepted. This study examines the discursive production of disability and disability research in the legal setting as the participants (investigators, attorneys, judges) sought to make sense of FC.